Target-Dependent Expression of IL12 by synNotch Receptor-Engineered NK92 Cells Increases the Antitumor Activities of CAR-T Cells - Luo, Hong; Wu, Xiuqi; Sun, Ruixin; Su, Jingwen; Wang, Yi; Dong, Yiwei; Shi, Bizhi; Sun, Yansha; Jiang, Hua; Li, Zonghai (Frontiers in Oncology, 2019)
IL12 is an immune-stimulatory cytokine for key immune cells including T cells and NK cells. However, systemic administration of IL12 has serious side effects that limit its clinical application in patients. Recently, synthetic Notch (synNotch) receptors have been developed that induce transcriptional activation and deliver therapeutic payloads in response to the reorganization of specific antigens. NK92 cell is a human natural killer (NK) cell line which has been developed as tools for adjuvant immunotherapy of cancer. Here, we explored the possibility of using synNotch receptor-engineered NK92 cells to selectively secrete IL12 at the tumor site and increase the antitumor activities of chimeric antigen receptor (CAR)-modified T cells. Compared with the nuclear factor of activated T-cells (NFATs) responsive promoter, which is another regulatory element, the synNotch receptor was better at controlling the expression of cytokines. NK92 cells transduced with the GPC3-specific synNotch receptor could produce the proinflammatory cytokine IL12 (GPC3-Syn-IL12-NK92) in response to GPC3 antigen expressed in cancer cells. In vivo GPC3-Syn-IL12-NK92 cells controlling IL12 production could enhance the antitumor ability of GPC3-redirected CAR T cells and increase the infiltration of T cells without inducing toxicity. Taken together, our results demonstrated that IL12 supplementation by synNotch-engineered NK92 cells could secrete IL12 in a target-dependent manner, and promote the antitumor efficiency of CAR-T cells. Local expression of IL12 by synNotch-engineered NK92 cells might be a safe approach to enhance the clinical outcome of CAR-T cell therapy.